NEW DITERPENES FROM SALVIA-PACHYSTACHYS - (:unkn) unknown (AMER SOC PHARMACOGNOSY, 1990)
Two new diterpenes, 2-alpha-hydroxyferruginyl-2,12-dimethyl ether and pachystazone (abiet-5-en-7-one) were isolated from Salvia pachystachys together with the known diterpenes cryptanol, taxodione, royleanone, horminone, sugiol, 15-hydroxyferruginol, and ferruginyl-12-methyl ether. The structure of the compounds were established by spectral methods.
Keywords: LEAF-GLAND PIGMENTS; ROOTS